2007
DOI: 10.1158/0008-5472.can-06-3362
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Is Expressed in Pancreatic Cancer and Stimulates Cell Proliferation and Invasion in an Autocrine Manner via the Adrenomedullin Receptor, ADMR

Abstract: The current study investigated adrenomedullin as a potential autocrine regulator of pancreatic cancer cell function. Adrenomedullin was localized in the neoplastic epithelium of 90% (43 of 48) of human pancreatic adenocarcinomas analyzed by immunohistochemistry and was expressed by 100% (8 of 8) of pancreatic cancer cell lines analyzed by reverse transcription-PCR. Pancreatic cancer cell lines also secreted adrenomedullin into the culture medium as determined by ELISA (5 of 5). Exogenous adrenomedullin treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 39 publications
7
86
1
Order By: Relevance
“…Several AM-overexpressing human carcinoma cell lines exhibit enhanced growth in vitro and in vivo to a varying degree (15,25). A recent report demonstrated that AMA inhibited the proliferation and invasion of pancreatic cancer cells expressing AM receptors in vitro (13). However, we found that neither AM nor AMA affected the growth of OS-RC-2 renal cancer cells in vitro, even though OS-RC2 tumor sizes in mice were clearly reduced by AMA.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Several AM-overexpressing human carcinoma cell lines exhibit enhanced growth in vitro and in vivo to a varying degree (15,25). A recent report demonstrated that AMA inhibited the proliferation and invasion of pancreatic cancer cells expressing AM receptors in vitro (13). However, we found that neither AM nor AMA affected the growth of OS-RC-2 renal cancer cells in vitro, even though OS-RC2 tumor sizes in mice were clearly reduced by AMA.…”
Section: Discussioncontrasting
confidence: 77%
“…AM gene knockout mice have shown embryonic lethality with severe abnormalities of the vasculature (10) and subcutaneous hemorrhage indicating the significance of AM signaling in vascular development. AM is expressed in a variety of malignant tumor tissues (11,12) and was shown to be mitogenic for human cancer cell lines, including lung, breast, colon, prostate and pancreatic lineages in vitro (12,13). In addition, AM is considered to be angiogenic in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CGRP receptor components and CGRP activity has been examined in several tumours and tumour-derived cell lines. For example, RAMP1 mRNA expression has been detected in benign and malignant pheochromocytomas (Thouennon et al 2010), Conn's adenoma (Forneris et al 2001) and pancreatic cancers (Ramachandran et al 2007).…”
Section: C5mentioning
confidence: 99%
“…objectIdZ146). Unfortunately, the original misidentification of this protein as an AM receptor continues to confuse a number of workers who refer to an 'ADMR' (AM receptor) based on L1/G10D (Ramachandran et al 2007(Ramachandran et al , 2009. It is particularly regrettable that the official gene name for L1/G10D has until recently been ADMR, perpetuating the unsubstantiated concept that this is a receptor for AM.…”
Section: What Constitutes An Am or A Cgrp Receptor?mentioning
confidence: 99%
“…Induced by hypoxia, AM involves in tumor angiogenesis, inhibiting apoptosis, immune escape and other processes which seem to have an important role in tumor growth, invasion, metastasis and other biological behaviors (1,2). Recent studies have indicated that AM highly expressed in ovarian cancer and its expression level was an important indicator of invasive ovarian cancer (1).…”
Section: Introductionmentioning
confidence: 99%